FOLFOXIRI plus Bevacizumab Versus FOLFOX plus Panitumumab for Metastatic Left‐Sided RAS/BRAF Wild‐Type Colorectal Cancer: Which "Side" Are You On?. (22nd February 2021) - Yu, Irene S.; Loree, Jonathan M.
Abstract: This commentary focuses on the results of the study by Pietrantonio et al., which evaluated the clinical conundrum of triplet versus doublet chemotherapy in combination with targeted therapy for metastatic left‐sided RAS / BRAF wild‐type colorectal cancer and appears in this issue. Both FOLFOXIRI [fluorouracil, leucovorin, oxaliplatin, and irinotecan] plus bevacizumab and FOLFOX [fluorouracil, leucovorin, and oxaliplatin] plus panitumumab have shown impressive activity in this population; however, the two have not been directly compared. The article by Pietrantonio et al. presents a propensity score‐adjusted analysis using information from five previous randomized trials and provides best available evidence comparing these regimens. This commentary will discuss their results and how their findings fit in current treatment paradigms. Abstract : This commentary focuses on recently reported results of a study evaluating the clinical conundrum of triplet versus doublet chemotherapy in combination with targeted therapy for metastatic left‐sided RAS/BRAF wild‐type colorectal cancer.